2013
DOI: 10.1021/jo400993y
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Oligoethyleneimine−β-Cyclodextrin “Click” Clusters for Enhanced DNA Delivery

Abstract: Monodisperse amphiphilic oligoethyleneimine (OEI)-β-cyclodextrin (βCD) clusters have been prepared, and their potential as gene delivery systems has been evaluated in comparison with a nonamphiphilic congener. The general prototype incorporates tetraethyleneimine segments linked to the primary rim of βCD through either triazolyl or thioureidocysteaminyl connectors. Transfection efficiency data for the corresponding CD:pDNA nanocomplexes (CDplexes) in BNL-CL2 murine hepatocytes evidenced the strong beneficial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 46 publications
0
19
1
Order By: Relevance
“…[24,25] Almost all reporteds upramolecular gene-delivery systems that exploit CD-inclusion capabilities are engineered from mac-romolecules bearing complementary host and guest moieties [26,27] or from small-molecule CD derivatives and macromolecular partners [28][29][30] in which at least one of the components has ap olycationic nature.T he combinationo fs everal elemental noncovalenti nteractions results in hierarchically ordered materials that can further condense nucleic acidsa nd mediate transfection.Although the flexibilityo ft he self-assembling process, its dynamic nature,a nd the facile optimization of supramolecular polycations bear some advantages relative to covalent polycations, the intrinsic polydisperse nature and random conformation of the macromolecular components represents al imitation for studies into structure-activity relationshipsa nd batch-to-batchr eproducibility.T he development of small-molecule-based supramolecular vectors for gene therapy has thus become an urgent need. To date, three different CD-based approaches have been proposed toward this goal: 1) linear redox-sensitive supramolecular polymers assembled from ad itopic b-CD host and ad itopic polycationic bisferrocene guest; [31] 2) multihead-multitail polycationic amphiphilic CDs (paCDs), which assemble in the presence of pDNA to form onionlike nanocomplexes (CDplexes) with alternating paCD bilayers and polynucleotide chains, although disordered in aqueous solution; [32][33][34][35][36][37] and 3) xylylene-capped CD-centered polycationic clusters that form dimers in aqueous media, which can bridge DNA fragments in ap H-dependent reversible manner [38] ( Figure 1). In spite of considerable success, the above approaches suffer from either low control over the elementary supramolecular speciesorr elativelyh igh synthetic cost, whichhamper further development.W ec onceivedt hat such drawbacks could be mitigated by using simple CD-centered polycationic clusters throught he implementationo fa na dditional level of self-assembly promoted by ditopic hosts.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] Almost all reporteds upramolecular gene-delivery systems that exploit CD-inclusion capabilities are engineered from mac-romolecules bearing complementary host and guest moieties [26,27] or from small-molecule CD derivatives and macromolecular partners [28][29][30] in which at least one of the components has ap olycationic nature.T he combinationo fs everal elemental noncovalenti nteractions results in hierarchically ordered materials that can further condense nucleic acidsa nd mediate transfection.Although the flexibilityo ft he self-assembling process, its dynamic nature,a nd the facile optimization of supramolecular polycations bear some advantages relative to covalent polycations, the intrinsic polydisperse nature and random conformation of the macromolecular components represents al imitation for studies into structure-activity relationshipsa nd batch-to-batchr eproducibility.T he development of small-molecule-based supramolecular vectors for gene therapy has thus become an urgent need. To date, three different CD-based approaches have been proposed toward this goal: 1) linear redox-sensitive supramolecular polymers assembled from ad itopic b-CD host and ad itopic polycationic bisferrocene guest; [31] 2) multihead-multitail polycationic amphiphilic CDs (paCDs), which assemble in the presence of pDNA to form onionlike nanocomplexes (CDplexes) with alternating paCD bilayers and polynucleotide chains, although disordered in aqueous solution; [32][33][34][35][36][37] and 3) xylylene-capped CD-centered polycationic clusters that form dimers in aqueous media, which can bridge DNA fragments in ap H-dependent reversible manner [38] ( Figure 1). In spite of considerable success, the above approaches suffer from either low control over the elementary supramolecular speciesorr elativelyh igh synthetic cost, whichhamper further development.W ec onceivedt hat such drawbacks could be mitigated by using simple CD-centered polycationic clusters throught he implementationo fa na dditional level of self-assembly promoted by ditopic hosts.…”
Section: Introductionmentioning
confidence: 99%
“…6,7) We studied the preparation of a 6-octa-substituted γ-CD derivative by the click reaction and found that microwave (MW) irradiation efficiently assisted the poly-modification with the click reaction.…”
Section: Cutting-edge Science Of Cyclodextrinmentioning
confidence: 99%
“…The circumstance that nanostructure-mediated non-viral nucleic-acid delivery is insufficiently developed yet for clinical applications has strongly motivated the research on novel synthetic amphiphilic cyclodextrin assemblies as potential non-viral gene carriers [ 43 , 45 , 46 , 61 , 62 , 63 , 64 , 80 ]. The successful entry of plasmid DNA (a multianionic macroion) into the living cells requires a complex formation between DNA and cationic carriers (CDplexes) enabling the DNA compaction and facilitating the CDplex adsorption at the negatively charged biomembranes towards cellular internalization and targeted delivery ( Figure 6 ).…”
Section: Supramolecular Assemblies Of Amphiphilic Cyclodextrinsmentioning
confidence: 99%
“…Table 3 presents valuable examples of recently reported applications of organized amphiphilic cyclodextrin assemblies [ 28 , 30 , 35 , 36 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. For a broader range of potential applications of cyclodextrin-based nanomaterials, the reader is advised to consult previous publications [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Potential Application Of Supramolecular Assemblies Of Ampmentioning
confidence: 99%